(untitled) (Verbum. Revista de teologie catolică, 2025)
Among his many theological contributions, St. Thomas Aquinas also composed a commentary on the Lord’s Prayer. In 1273, a year before his death, the Dominican theologian was invited to Naples to preach the Lenten Sunday homilies. On this occasion, he proposed a catechetical itinerary structured around the three theological virtues: faith, hope, and charity. To cultivate faith, he expounded the Nicene-Constantinopolitan Creed, outlining the truths to be believed; to foster hope, he explained the two principal prayers—the Our Father and the Hail Mary—highlighting the goods to be hoped for; and to encourage charity, he commented on the Decalogue, as the practice of the commandments grounded in love. This article traces Aquinas’ theological method in these Lenten instructions, emphasizing his capacity to synthesize the Christian faith through biblical exegesis and the patristic tradition.